FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PENERIMAAN PAJAK - WELDY FERDIANTA; AAN MARLINAH (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
This research to analyze influence consciousness taxpayers, tax services, tax compliance, tax audits, tax collection, obligation to have tax number, toward tax revenue. This research conducted at Kantor Pelayanan Pajak Pratama Kalideres in the West Jakarta on 2017.This research is casual comparative sample approach taken by purposive sampling technigue with a total sample of 124 respondents. Methods of data collection on issues related to research carried out using a questionnaires. Data analysis in this research uses with SPSS program. The result showed that Tax Services and Tax compliance have influence toward Tax Revenue. But the Consciousness Taxpayers, Tax Audits, Tax Collection, and Obligation to Have Tax Number do not influence toward Tax Revenue,